Caltsacoryne setouchiensis (Hydrozoa, Anthoathecata) a new genus and species of hydrozoan jellyfish from Japan - Toshino, Sho; Hamatsu, Yoshimi; Uchida, Hiroaki (Zootaxa, 2021)
We report a new genus and species of hydrozoan jellyfish belonging to the order Anthoathecata collected from the Seto Inland Sea, western Japan. Caltsacoryne setouchiensis gen. et sp. n. can be distinguished from other species of Corynidae based on the following combination of morphological characters: number of tentacles, cnidocyst pads, manubrium length, and the shape of the gonad and tentacles. A table comparing the primary diagnostic characters of this new genus of Corynidae is presented.